(untitled) (Swiss Medical Weekly, 2017)
QUESTIONS UNDER STUDY Chronic pain has a high impact on individuals and society. (Cost-)effective interventions are desperately needed. We evaluated short- and long-term effects of the Bern Ambulatory Interprofessional Rehabilitation (BAI-Reha) for patients with chronic musculoskeletal pain. METHODS We analysed data prospectively collected from patients with chronic musculoskeletal pain before and after BAI-Reha (at 12 weeks, 1 year and 2 years) using linear mixed-models and logistic generalised estimating equations. RESULTS The first thirty consecutive patients with chronic musculoskeletal pain, aged between 20 and 73 years (mean 44.83, standard deviation 12.57 years) were included. We found significant changes over time compared with baseline for return to work (p <0.001), Euro quality of life visual analogue scale score (p = 0.026), burden of suffering (p = 0.001), self-rated and observed quality of daily life task motor performance (p <0.001 and p = 0.012, respectively) but not for pain intensity (p = 0.16) and observed quality of daily life task process performance (p = 0.28). At the first postintervention visit we found significant differences compared with baseline in return to work (odds ratio 5.26, 95% confidence interval [CI] 1.80–15.39], burden of suffering (mean difference 5.26, 95% CI 2.09–8.44], self-rated quality (mean difference 2.31, 95% CI 1.57–3.05) and satisfaction (mean difference 2.80, 95% CI 1.95-3.66) with daily life task performance, and observed quality with daily life task motor performance (mean difference 0.31, 95% CI 0.02–0.60). CONCLUSIONS This study confirms earlier data and supports the effectiveness of interprofessional rehabilitation for patients with chronic musculoskeletal pain.